Immune resilience : the breakthrough plan to protect your body and fight disease - Hodges, Romilly (Avery, an imprint of Penguin Random House LLC., 2022)
"Some people can fight off infections relatively easily, with minor symptoms, while others suffer severely. But these outcomes--and our immune responses against them--aren't fixed; we can build immune resilience. But how? The answer goes beyond popping vitamin C and zinc during flu season. As clinical nutritionist Romilly Hodges reveals, our immune system is intricate and multifaceted, and powerfully impacted by what we eat, as well as by our lifestyle routines. Immune Resilience offers a fascinating tour of the incredible ways our bodies protect us against disease, with assessments throughout to help the reader identify their weak areas. Then it outlines a personalized, step-by-step program blending defense-building foods with lifestyle strategies, including important advice on movement, sleep, and stress-relief. This book explains: the connection between sleep and immune memory; how you can harness the power of gentle fasting; why good germs increase immunity and decrease allergies and asthma; how to prepare nutrient-packed meals, with recipes; what kind of exercise boosts immunity, and more." --